2022
DOI: 10.1093/mnras/stac2060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the environment and feedback physics on the initial mass function of stars in the STARFORGE simulations

Abstract: One of the key mysteries of star formation is the origin of the stellar initial mass function (IMF). The IMF is observed to be nearly universal in the Milky Way and its satellites, and significant variations are only inferred in extreme environments, such as the cores of massive elliptical galaxies and the Central Molecular Zone. In this work we present simulations from the STARFORGE project that are the first cloud-scale radiation-magnetohydrodynamic simulations that follow individual stars and include all re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 139 publications
1
14
0
Order By: Relevance
“…For example, in preferential attachment phenomena and diffusion-limited aggregation, a large number of random processes (instead of a single stochastic event) determine the outcome, which becomes highly deterministic. The state-of-art star cluster formation simulation, STAR-FORGE, appears to support this view (Guszejnov et al 2022). Despite the chaotic and complex physical processes involved, the simulated maximum stellar masses in embedded star clusters 1 presented by these latter authors seem to have too little scatter to be explained by stochastic sampling schemes and to show strong evidence of a correlation between the embedded star cluster mass and the mass of the most massive star (m max −M ecl relation), which is consistent with optimal sampling.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, in preferential attachment phenomena and diffusion-limited aggregation, a large number of random processes (instead of a single stochastic event) determine the outcome, which becomes highly deterministic. The state-of-art star cluster formation simulation, STAR-FORGE, appears to support this view (Guszejnov et al 2022). Despite the chaotic and complex physical processes involved, the simulated maximum stellar masses in embedded star clusters 1 presented by these latter authors seem to have too little scatter to be explained by stochastic sampling schemes and to show strong evidence of a correlation between the embedded star cluster mass and the mass of the most massive star (m max −M ecl relation), which is consistent with optimal sampling.…”
Section: Introductionmentioning
confidence: 93%
“…Kirk & Myers (2012) find that massive stars can be better described if they assume an older cluster age (2 Myr instead of 1 Myr). This suggests that stars with different masses in the same star cluster may have different average ages and a single age assumption may introduce bias to the mass estimation of these pre-main sequence stars; see also STARFORGE simulations where more massive stars in a star cluster form at a later time (Guszejnov et al 2022). In addition, the statistical uncertainty on individual stars due to different extinction estimation errors and multiplicity are neglected.…”
Section: Uncertainties From Kirk and Myersmentioning
confidence: 99%
“…This result is at odds with the results of Bate (2019) who find that under present-day conditions the characteristic stellar mass is quite independent of the metallicity (ranging from 1/100 to 3 times the solar value). This may be due to the limited resolution of the Guszejnov et al (2022) study -as mentioned above, Bate (2019) found that at low metallicity the effects of intermediatedensity gas being hotter were offset by enhanced cooling at high densities that led to enhanced small-scale fragmentation. On the other hand, Guszejnov et al (2022) found that subjecting solar-metallicity clouds to a stronger ISRF increased the characteristic stellar mass, which is in qualitative agreement with the results we present here.…”
Section: Comparison With Previous Theoretical Modelsmentioning
confidence: 96%
“…In another recent paper, Guszejnov et al (2022) studied how environment, initial conditions, and feedback may alter the stellar IMF. Among other results, they find that the characteristic stellar mass varies with metallicity and with the level of the ISRF.…”
Section: Comparison With Previous Theoretical Modelsmentioning
confidence: 99%
See 1 more Smart Citation